Black students' experiences of transformation at UCT : a photovoice study - Cornell, Josephine Ruth (Department of Psychology, 2015)
South African higher education has faced much structural transformation since the end of apartheid, and yet remains a racialised space. It is clear that despite a stated commitment to transformation in university policy nationally, in reality there is much ambivalence around transformation. In debates around transformation, black students are frequently represented in stigmatising ways. These negative representations are part of a discourse that holds the increasing numbers of black students responsible for lowering university standards. When black students encounter these discourses it can affect their self-esteem and academic performance. This study thus explores black students’ experiences of transformation at the University of Cape Town (UCT). Over six months, 10 black African and coloured UCT students participated in a photovoice research project. They participated in focus groups and produced personal reflections, photographs and written stories representing their experiences and perspectives on transformation in higher education in a previously white University. This data was analysed using thematic analysis, within a critical psychological framework, specifically decolonising psychologies. The participants’ everyday experiences of UCT were explored, and four themes were evident: the narrowness of UCT’s transformation focus; the prevalence of racial stereotypes on campus; the Eurocentric focus of the university; and the racialisation of space on campus. Ultimately, it appears that whiteness is dominant at UCT. This detrimentally affects many black students who are required to learn within this often unwelcoming white space, and who internalise the negative stereotypes they encounter. Nevertheless, many black students succeed. The participants in this study employed a variety of coping mechanisms to help them navigate through life at UCT. They were also able to employ strategies to resist the dominant discourse of black inferiority, and to re-present themselves and transformation on their own terms.